2012
DOI: 10.1002/joc.3446
|View full text |Cite
|
Sign up to set email alerts
|

Recent climate change in the Arabian Peninsula: annual rainfall and temperature analysis of Saudi Arabia for 1978–2009

Abstract: ABSTRACT:The rainfall and temperature climatology over the Arabian Peninsula are analysed on an annual basis using various gridded datasets. For Saudi Arabia, the area of which represents almost 80% of the Peninsula, the climatic datasets from its 27 ground observations are analysed for the period 1978-2009, with additional gridded datasets used to describe the observed state and change of the present climate. The gridded datasets represent well the very dry (40-80 mm) area over the world's largest sand desert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
204
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(237 citation statements)
references
References 25 publications
(38 reference statements)
13
204
2
Order By: Relevance
“…In contrast, the high-rainfall types (e.g., C) tend to decrease. Almazroui et al (2012) found a statistically significant decrease (47.8 mm/decade) in the annual rainfall over Saudi Arabia from 1978 to 2009. It can therefore be implied that the dry periods in the last decades can be related to a weakening of the cyclonic conditions and intensification of the anti-cyclones.…”
Section: Trend Analysis In Observed Weather Typesmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, the high-rainfall types (e.g., C) tend to decrease. Almazroui et al (2012) found a statistically significant decrease (47.8 mm/decade) in the annual rainfall over Saudi Arabia from 1978 to 2009. It can therefore be implied that the dry periods in the last decades can be related to a weakening of the cyclonic conditions and intensification of the anti-cyclones.…”
Section: Trend Analysis In Observed Weather Typesmentioning
confidence: 89%
“…One possible explanation for this deficit is the lack of a complete, reliable and homogenized dataset of rainfall, that also provides a reasonable spatial coverage. Those studies that have sought to describe the spatial patterns of climate in Saudi Arabia have generally relied on a very limited number of observatories of short duration (e.g., Ahmed, 1997;Abdullah and Almazroui, 1998;Rehman, 2010;Almazroui et al, 2012). Among these, Ahmed (1997) employed factor analysis to classify Saudi Arabia into distinct climate regions, using 14 climate variables from a spatially restricted data set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge and prediction of wet and dry spell probability occurrence, rainfall variability, shifts, and trends are critical when considering the impact of the climate change and can be estimated with reliability from reasonably available records. Wet and dry sequences are treated by different authors (Feyerhem and Bark 1965;Lioubimtseva 2004;Şen 2009;Almazroui et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the climatic conditions of this region have focused on the inland areas of bigger countries such as Saudi Arabia and Iran (Almazroui et al 2012Rahimzadeh et al 2009), and there have been few studies on the climatic conditions of other countries such as Bahrain and Qatar (Brooks and Rogers 2000;Shi et al 2004). Moreover, these studies have focused mainly on interannual variations of weather, with only very limited consideration of seasonal variations, e.g., for Saudi Arabia and Kostopoulou et al (2014) for the entire eastern Mediterranean and Middle East region.…”
Section: Introductionmentioning
confidence: 99%